An Analysis of Loan Loss Provision Behavior in US Banking - Luo, Tianyi (2019)
This research aims to test the determinants of loan loss provision practices of the top 80 US commercial banks from 2012 to 2018. Firstly, utilizing Stochastic Frontier Analysis, this study constructs the efficiency frontiers to estimate efficiency score for the sample banks. The average efficiency score for US banks is approximate 90.1%, which indicates a relatively high efficiency gain. Secondly, this study employs Generalized Method of Moments estimators to find the dominant determinants of provisioning practices in US and test the several hypotheses. Referring to the main hypotheses, this study, therefore, investigates income smoothing, capital management, business cycle, and cost efficiency hypotheses. Specifically, this study finds that provisioning practices mainly to be procyclical. Besides, the empirical findings also support income smoothing and capital management hypotheses. However, this study cannot find any evidence concerning the correlation between cost efficiency and provisioning.